A mediaeval court physician at work: Ibn Jumay''s commentary on the Canon of Medicine - Nicolae, D; Daniel Nicolae (2012)
Ibn Jumay''s (d. c. 594/1198) commentary on the Canon of Medicine by Ibn Sīnā (d. 428/1037) occupies an important place in the history of medicine for it is the first Canon commentary written by a physician and thus stands at the start of a tradition extending over 500 years. In addition, it is a so-far neglected source for our understanding of mediaeval Islamic medicine. The present thesis analyses the commentary with the aims of (1) determining the methods by which the court physician composed his treatise and (2) understanding why Ibn Jumay' undertook to prepare a commentary on one of the most thorough medical compendia of the middle ages. Chapter One presents the biography of Ibn Jumay', reveals that his religion had little impact on his writings and surveys his library which played a pivotal role in the composition of the commentary. Chapter Two investigates Ibn Jumay''s methodology in the entire commentary; it reveals that with his philological and source-critical methods Ibn Jumay' wanted to establish an authoritative reading of the Canon and to demonstrate the high degree of his erudition. Chapter Three focuses on selected passages in the commentary in form of three case studies. Ibn Jumay''s comments on anatomy/dissection, assorted materia medica and headaches demonstrate the court physician’s reverence for ancient authorities and his quest to revive and refine their teachings. Chapter Four contextualises Ibn Jumay''s methods and agenda by comparing them to those of other relevant scholars of the twelfth and thirteenth centuries. The thesis concludes by arguing that Ibn Jumay''s commentary was part of his revival of the art of medicine and his attempt to gain power in the medical tradition by attaching his name to one of the greatest scholars of his time — the ra'īs Ibn Sīnā.